Aáeáing irrigation performance with comparative indicators : The case of the Alto Río Lerma irrigation District, México - Kloezen, Wim H.; Garcés-Restrepo, Carlos (Colombo (Sri Lanka), 1998)
Sumario (En)
Ilus.; 34 ref.
Keywords: RIEGO; SITUACION ECONOMICA; ABASTECIMIENTO DE AGUA; PRODUCTIVIDAD DE LA TIERRA; MEXICO